Effect of Chitosan Coating on Physical and Microbial Characteristics of Fresh-Cut Green Peppers (Capsicum annuum L.) - Raymond, L.V.; Zhang, M.; Azam, S.M. Roknul (Pakistan Journal of Nutrition, 2012)
Edible coatings, thin layer formed on the surface of a product, have been used to preserve fresh-cut fruits and vegetables since they can improve quality by affecting respiration and moisture loss. Green pepper slices were subjected to chitosan coating treatment achieved by dipping, afterwards stored at 5°C for a period of 15 days. The effect of various chitosan concentrations (0%, 0.5%, 1.0% and 2% (w/v) chitosan) on some physico-chemical and microbial characteristics of the slices was subsequently analyzed during storage. The data indicated that the performance of chitosan treatments was better than that of control. The decrease of surface lightness was delayed by chitosan treatments; and the surface green colour was kept under marginal changes compared to control. On the other hand, a greater reduction of fungal incidence, carbon dioxide concentration and electrolyte leakage of the chitosan treated samples was observed with increased chitosan concentration treatment. Microbiological evaluation revealed that total viable cells count decreased with increasing chitosan concentration. This correlated well with the external changes which were affected to a lesser extent in the 2% chitosan compared to the control; in addition, delaying of changes was significantly chitosan concentration dependent.